PAROUSIA, PEMBENARAN ALLAH, DAN KEBANGKITAN ORANG MATI: PERBUATAN-PERBUATAN BAIK DALAM MERAIH KESELAMATAN MENURUT SURAT-SURAT PAULUS - Demianus Nataniel (Sekolah Tinggi Theologia Abdiel, 2018)
This article focuses on the good works in receiving the salvation in Pauline Letters. It contains of debating on faith and the good works relationship in The New Perspectives on Paul. By exploring some themes relating to Paul’s concept of salvation in his Letters, namely: parousia, justification, and the resurrection, this article shows that the good works are essensial part in receiving God’s saving work. This conclusion is based on some texts in Pauline Letters that shows Paul’s exhortation that asked and urged Christians to do good works in order to welcome parousia.